A tireless scholar: V.I. Semevsky's work at the Department for Self-Education Promotion - S.V. Gavrilov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper discusses the peculiarities of V.I. Semevsky's work as a secretary of the Department for Self-Education Promotion at the Pedagogical Museum of Military Educational Establishments and a compiler of the encyclopedic reading program for self-study and the program on Russian history. The relevance of this study is determined by the absence of works on the activity of this historian-narodnik as a popularizer of historical knowledge in modern Russian historiography. To achieve the goal of the research, historical-genetic, retrospective, and biographical methods, as well as the method of system analysis have been used. The following conclusions have been made as a result of the study of the vast source base. The historian was the permanent secretary of the Department for Self-Education Promotion, kept minutes of meetings, carried out written and spoken consultancy of interested individuals, conducted business correspondence of the Department, became a compiler of the encyclopedic reading program for self-study and the program on Russian history. The main objective of V.I. Semevsky and his associates was formation of a certain worldview within commoner intelligentsia using a variety of methods: organizing public lectures, preparing educational programs on natural sciences and the humanities, publishing. The activity of the Department and, in particular, V.I. Semevsky became a noticeable phenomenon in the cultural life of the capital despite it gave rise to numerous discussions in the periodical press. V.I. Semevsky's scrupulous efforts contributed to effective functioning of the Department on the development of the system of self-education in Russia in the late 19th – early 20th centuries, consolidating the writing team, organizing the readers' feedback, conducting diversified public readings. Over almost twenty years of the activity of the Department, six editions of “Reading Programs for Self-Study” with a total circulation of about 100 thousand copies were issued.